E-SERVQUAL, PROMOSI DAN LOYALITAS PELANGGAN MARKETPLACE - Firda Nosita (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2020)
The study aims to determine the effect of E-ServQual and promotions on marketplace customer loyalty. Both factors can be a consideration of customer’s decision to make a purchase in marketplace. Previous shopping experience is the basis for repurchase decision that lead to the loyalty on a marketplace. The study was conducted on 100 students of the Pancasetia School of Economics in Banjarmasin by share online questionnaire. By using multiple linear regression analysis, it was found that both E-ServQual and promotion had a significant effect on marketplace customer’s loyalty. An excellent E-ServQual shows that the marketplace is able to guarantee the security of customer’s transaction. In addition, the marketplace also allows customers to communicate directly with sellers, find out the transaction status dan provide features which makes customers experience a convenience shopping. Promotion becomes an important part that cannot be ignored by the marketplace. The form of promotions such as coupons, discounts, bonuses, and loyalty programs have proven to be a factor that is considered by customer to make repeat purchase aimed at creating loyalty.